Rituximab Concentration Varies in Patients With Different Lymphoma Subtypes and Correlates With Clinical Outcome - Liu, Shu; Wang, Zhao; Chen, Rongxin; Wang, Xueding; Fang, Xiaojie; Chen, Zhuojia; Guan, Shaoxing; Liu, Tao; Lin, Tongyu; Huang, Min; Huang, He (Frontiers in Pharmacology, 2022)
Individual variations in concentrations of rituximab in different B cell non-Hodgkin’s lymphoma subtypes and their relevance to efficacy were still unclear. From 2016 to 2021, a prospective clinical trial was conducted, and 510 samples with 6 uncommon subtypes of B-cell lymphoma were enrolled to examine the pharmacokinetic behaviour of rituximab and its impact on clinical outcomes, including complete response (CR), progression-free survival (PFS) and overall survival (OS). Considerable variability was observed in the rituximab trough concentration in the first cycle (C1-trough, 1.16 μg/mL to 55.52 μg/mL) in patients with different lymphoma subtypes. Patients with "double-hit" lymphoma (4.01±0.77 μg/mL) or mantle cell lymphoma (MCL; 15.65±16.45 μg/mL) had much lower C1-trough and worse outcomes. Great individual variation in the C1-trough existed among patients with mucosa-associated lymphoma (MALT), and the high C1-trough observed in patients treated with the RB regimen was associated with a better response than was obtained with R-CHOP (38.41±14.13 μg/mL vs. 15.49±8.80 μg/mL, P=0.0029). Despite the high aggressiveness of the cancer, Burkitt lymphoma patients receiving intensive chemotherapy had the highest C1-trough (28.85 ± 9.35 μg/mL) and maintained long-term PFS. The C1-trough in patients with mixed, unclassifiable B-cell lymphoma was close to 20 μg/mL, and these patients had acceptable outcomes. Overall, a low rituximab C1-trough was associated with adverse consequences, including persistent progression, early recurrence and a short OS, however, some high-risk factors appeared to be balanced by the presence of a high C1-trough. Basal levels of circulating CD19+ lymphocytes differed between and within patients with diverse lymphoma subtypes and were negatively correlated with C1-trough. Therefore, the traditional doses of rituximab are inadequate for patients with "double-hit" lymphoma and MCL. Increasing the initial rituximab dose according to the disease, high-risk factors and even the baseline CD19+ lymphocyte count will be new methods to optimize therapeutic regimens for patients with different lymphoma subtypes. ChiCTR1800017001 (http://www.chictr.org.cn/index.aspx).